Preliminary study on the critical success factors of shopping mall developments in Klang Valley, Malaysia - Quek, Xin Ying; Anuar Alias, (Penerbit Universiti Kebangsaan Malaysia, 2022)
n Malaysia, shopping malls have contributed a lot to the speedy growth of the tourism sector. Thus, successful operation of shopping malls should be a serious responsibility for mall owners and mall managers. This paper is an initial exploration of the factors that are critical for shopping mall in Malaysia. The aim of this paper is to primarily investigate what are the Critical Success Factors for shopping mall developments in Malaysia. The content analysis of Literature Review has been adopted as the methodology to identify the Critical Success Factors. The topic regarding Critical Success Factors for shopping mall development can be further studied in the future by using this paper as the fundamental study. A more comprehensive and thorough study could be done by investigating the perception of the professionals in retail-related field to arrive at a more reliable approach for the success of shopping mall developments. The research methodologies and data analysis methods to be adopted in the further study are proposed in this paper.